2006
DOI: 10.3892/ijo.29.3.649
|View full text |Cite
|
Sign up to set email alerts
|

The expression of the carboxyl ester lipase gene in pancreas and pancreatic adenocarcinomas

Abstract: Abstract. Since pancreatic cancer is an aggressive and often incurable malignancy, we investigated if the carboxyl ester lipase gene (CEL) is specifically expressed in pancreatic tissues and its promoter can be used for a specific suicide gene approach. Twenty-five tumor samples, 24 samples of normal pancreatic tissue and control tissues from other organs were examined by radioactive in situ hybridization (ISH) to localize CEL mRNA. Two carcinoma samples and 6 permanent cell lines were examined by reverse tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
(20 reference statements)
3
6
0
Order By: Relevance
“…Excluding lymph nodes, the distribution of BCL10 immunostaining, identified with the monoclonal (331.3) antibody, among normal and ectopic pancreas, acinar metaplasia, and ACCs well reflected that of CEH. Our results on CEH distribution (Table 2) are in line with those previously published, since CEH was found in the pancreas and lactating breast, while neither CEH protein nor mRNA were observed in other normal tissues, with the exception of the gastric mucosa [9,10,[12][13][14][27][28][29].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Excluding lymph nodes, the distribution of BCL10 immunostaining, identified with the monoclonal (331.3) antibody, among normal and ectopic pancreas, acinar metaplasia, and ACCs well reflected that of CEH. Our results on CEH distribution (Table 2) are in line with those previously published, since CEH was found in the pancreas and lactating breast, while neither CEH protein nor mRNA were observed in other normal tissues, with the exception of the gastric mucosa [9,10,[12][13][14][27][28][29].…”
Section: Discussionsupporting
confidence: 94%
“…In addition, the fact that we did not find BCL10-IR in other pancreatic tumors confirms that BCL10 immunohistochemistry is highly specific in detecting pancreatic acinar cell differentiation. Moreover, the lack of CEH expression in pancreatic tumors other than ACCs is in agreement with the findings reported by Reuss et al [27].…”
Section: Discussionsupporting
confidence: 90%
“…We observed that CEL expression disappeared when acinar-toductal metaplasia was present, confirming that the protein is a marker of pancreatic acinar cells only when these remain polarized and in acini-like arrangement. Our results are consistent with those of Reuss and coworkers (39). When they examined 25 ductal or mucinous adenocarcinomas from the pancreas, all cases were negative for CEL mRNA by in situ hybridization.…”
Section: Discussionsupporting
confidence: 93%
“…CEH is a glycoprotein secreted by pancreatic acinar cells [10] and lactating mammary gland [11] involved in cholesterol and lipid-soluble vitamin ester hydrolysis and absorption. It has been previously observed in pancreatic acinar cell carcinomas [12,13] but not in pancreatic ductal adenocarcinomas. As recently demonstrated by La Rosa et al [14], its presence in tumour cells may be proved immunohistochemically using a specific anti-CEH antibody as well as an anti-C-terminal BCL10 monoclonal antibody, because the C-terminal extremities of both CEH and BCL10 protein share the same amino acidic sequence.…”
Section: Resultsmentioning
confidence: 85%